2020
DOI: 10.1111/andr.12944
|View full text |Cite
|
Sign up to set email alerts
|

Seminal plasma components from fertile stallions involved in the epididymal sperm freezability

Abstract: Background Seminal plasma (SP) plays a crucial role in sperm protection and functionality. However, the effect of SP on the sperm cryopreservation is dependent on the stallion and SP composition. The use of epididymal spermatozoa incubated in the presence of SP could help the identification of the components of SP that are able to confer protection upon the spermatozoa during freezing. Objective The aims of this study were (i) to identify SP components involved in the potential protection of epididymal spermat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 79 publications
(90 reference statements)
0
10
0
Order By: Relevance
“…This phenomenon extends to sperm rich in polyunsaturated fatty acids (PUFA). However, the exact mechanism inherent to functionality of fatty acid in cryotolerance remains unclear, even though cells with higher levels of PUFA have an enhanced level of membrane flexibility and fluidity that is granted by PUFA with many double bonds [ 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon extends to sperm rich in polyunsaturated fatty acids (PUFA). However, the exact mechanism inherent to functionality of fatty acid in cryotolerance remains unclear, even though cells with higher levels of PUFA have an enhanced level of membrane flexibility and fluidity that is granted by PUFA with many double bonds [ 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The selected protein bands were spliced in approximately 2 × 2 mm parts and prepared for the digestion process as previously reported 86 , 87 . The bands were washed twice with Milli-Q water and then twice with 25 mM ammonium bicarbonate buffer pH 8.5 in 50% v/v acetonitrile during 30 min at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The separation and analysis of the tryptic digests of the samples were performed as previously described 86 , 87 , with a HPLC/MS system consisting of an Agilent 1290 Infinity II Series HPLC (Agilent Technologies, Santa Clara, CA, USA) equipped with an Automated Multisampler Module and a High-Speed Binary Pump, connected to an Agilent 6550 Q-TOF Mass Spectrometer (Agilent Technologies, Santa Clara, CA, USA) using an Agilent Jet Stream Dual electrospray (AJS-Dual ESI) interface. Experimental parameters for HPLC and Q-TOF were set in the MassHunter Workstation Data Acquisition software (Agilent Technologies, Rev.…”
Section: Methodsmentioning
confidence: 99%
“…Pivotal studies have reported that lauric, myristic, and oleic acids were two-fold more abundant in spermatozoa collected from stallions considered good freezers [ 187 ]. Furthermore, according to Vieira et al [ 188 ], spermatozoa with large amounts of docosahexaenoic acid (DHA) and stearic acid presented with superior post-thaw motility. However, the specific mechanisms underlying the role of fatty acids in sperm cryotolerance remain by and large unknown, even though cells with a high proportion of PUFAs have a higher degree of membrane fluidity and flexibility, which is provided by an abundance of double bonds present in the fatty acid chains [ 189 ].…”
Section: Fatty Acidsmentioning
confidence: 99%